COMPARATIVE POSTOPERATIVE ANALGESIA WITH FEMORAL NERVE BLOCK ”3-IN-1” AND WITH FASCIA ILIACA COMPARTMENT NERVE BLOCK AFTER HIP ALLOARTHROPLASTY - Stojiljković, Miloš P. (Medicinski časopis, 2016)
Hip arthroplasty is one of the most common operations in elderly population. Pre- and postoperative risks increase their postoperative morbidity and mortality. One of the most important factors, which is included in the perioperative risks, is pain. Control of postoperative pain diminishes incidence and severity of complication afterwards. We compared three different techniques of pain control in 30 patients scheduled for elective hip arthroplasty: 1) pharmacological - morphine 5 or10 mg iv q6h, depending on body weight, paracetamol 1 g IV q6h (MP), 2) nerve block: femoral nerve block, single shot (FNB) and 3) fascia iliaca compartment nerve block (FICNB). Measurement of pain intensity was performed with numerical pain scale (NPS). Systolic blood pressure and consumption of additional analgesics on demand were monitored, as well as the duration of nerve blocks. Both nerve blocks produced significantly lower pain scores than the purely pharmacological approach (MP 5.4+0.6 vs. FNB 2.8+1.6 and FICNB 2.9+1.2 after first postoperative hour). Consequently, the first group required more additional morphine and paracetamol after first hour compared to FNB and FICNB groups. Morphine was significantly more frequently added in the MP group (3.4+0.4 mg/kg IV) than in the FNB (2.1+0.5 mg/kg IV) and FICNB (2.5+0.4 mg/kg IV). Maximal duration of analgesia was 5 hours in MP group compared to 9 and 8 hours after FNB and FICNB, respectively. Postoperative analgesia with blocks enables better pain control, better cardiovascular stability and less adverse effect than the classical morphine-based analgesia.